How does completing a dissertation transform undergraduate students' understandings of disciplinary knowledge?. Issue 4 (19th May 2017) - Ashwin, Paul; Abbas, Andrea; McLean, Monica
Abstract : Dissertations are positioned as the capstone of an undergraduate degree, bringing together what students have previously learned from their programmes through a piece of independent research. However, there is limited research into the ways in which engaging in a dissertation has an impact on students' understandings of disciplinary knowledge. In this article, we explore the relations between students' accounts of sociological knowledge in their second and third years and how they engage with sociological knowledge in their dissertations. We argue that for the work of the dissertation to have an impact on students' understanding of sociological knowledge, students need to see their discipline as providing a way of answering their research questions. We explore the implications of this argument for both our understanding of the role of dissertations and research-based learning in universities more generally.